2016
DOI: 10.1016/j.cub.2015.12.064
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Reactive Oxygen Species Drive Apoptosis-Induced Proliferation via Drosophila Macrophages

Abstract: Summary Apoptosis-induced proliferation (AiP) is a compensatory mechanism to maintain tissue size and morphology following unexpected cell loss during normal development, and may also be a contributing factor to cancer and drug resistance. In apoptotic cells, caspase-initiated signaling cascades lead to the downstream production of mitogenic factors and the proliferation of neighbouring surviving cells. In epithelial cells of Drosophila imaginal discs, the Caspase-9 ortholog Dronc drives AiP via activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
276
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 182 publications
(286 citation statements)
references
References 50 publications
9
276
1
Order By: Relevance
“…Reactive oxygen species (ROS) are produced rapidly after damage and act as chemoattractants for macrophages. This has been demonstrated in both the imaginal disc [41] and the embryo [42] and ROS are required for activation of JNK and p38 [40]. In embryonic wounds, the NADPH oxidase DUOX, which acts as a source of H 2 O 2 , is activated by calcium, and Ca 2+ flashes have been found upon damage [43].…”
Section: Wound Healing and Early Responses To Tissue Damagementioning
confidence: 99%
“…Reactive oxygen species (ROS) are produced rapidly after damage and act as chemoattractants for macrophages. This has been demonstrated in both the imaginal disc [41] and the embryo [42] and ROS are required for activation of JNK and p38 [40]. In embryonic wounds, the NADPH oxidase DUOX, which acts as a source of H 2 O 2 , is activated by calcium, and Ca 2+ flashes have been found upon damage [43].…”
Section: Wound Healing and Early Responses To Tissue Damagementioning
confidence: 99%
“…Pioneering work in the Drosophila wing disc and eye has identified a requirement for JNK, Shh, EGF and TNF signaling pathways during apoptosis-induced compensatory proliferation [66][67][68][69]. In Drosophila imaginal discs, JNK activation in dying and neighboring cells depends on an inflammatory response that is triggered by Duox, which produces extracellular reactive oxygen species (ROS) [70 ]. Interestingly, hemocytes (macrophages) are required for ROS-mediated apoptosis-induced compensatory proliferation.…”
Section: Identifying New Molecules/pathways Important For Hair Cell Rmentioning
confidence: 99%
“…Two recent reports, including our own, demonstrated that repair processes in imaginal discs also require ROS 9,15 . In the first report, ROS were generated in response to a short pulse of apoptosis in larval wing imaginal discs.…”
Section: Synopsis Of Our Recently Published Workmentioning
confidence: 88%